Two mammalian MAGOH genes contribute to exon junction complex composition and nonsense-mediated decay - Singh, Kusum Kumari; Wachsmuth, Laurens; Kulozik, Andreas; Gehring, Niels H (RNA biology, 2013)
The exon junction complex (EJC) participates in the regulation of many post-transcriptional steps of gene expression. EJCs are deposited on messenger RNAs (mRNAs) during splicing and their core consists of eIF4A3, MLN51, Y14, and MAGOH. Here, we show that two genes encoding MAGOH paralogs (referred to as MAGOH and MAGOHB) are expressed in mammals. In macrophages, the expression of MAGOHB, but not MAGOH mRNA, increases rapidly after LPS stimulation. Both MAGOH proteins interact with other EJC components, incorporate into mRNA-bound EJCs, and activate nonsense-mediated decay. Furthermore, the simultaneous depletion of MAGOH and MAGOHB, but not individual depletions, impair nonsense-mediated decay in human cells. Hence, our results establish that the core composition of mammalian EJCs is more complex than previously recognized.
Published online: 23 Jul 2013
Gesehen am 02.02.2022